The effect of temperature and pyrolysis time of plastic waste in producing methane - Holisha Widiyanto; Boima Situmeang; Dina Alva Prastiwi; Ninik Triayu Susparini; Isna Laitusholihah (Pascasarjana Universitas Negeri Medan, 2022)
Plastic waste is a major environmental problem due to its widespread presence and lack of economic value. Pyrolysis is a process that can decompose plastic waste and produce methane gas, liquid, and solid products. This study aimed to investigate the factors that affect methane gas production and the amount of methane gas produced during the pyrolysis of various plastics, including a black plastic bag and plastic with aluminium foil. The results showed that the aluminium foil plastic produced more methane gas than the black bag, with optimal gas content at 7.74% for the aluminium foil plastic and 3.48% for the black bag. The type of plastic, time, and temperature all significantly affected the yield of methane gas produced. In addition, the interaction between variables in plastic type, time and temperature greatly affects the yield of methane gas (CH4) obtained, because the type of plastic F count (2904) is higher than F table 0.05 (4.00), at temperature F count (5449) is greater than F table 0.05 (2.76), when F count (746) is greater than F table 0.05 (2.76). In conclusion, the snack foil produced more methane gas than the black bag because it was made of low-density polyethylene and contained aluminium ions that catalysed the decomposition of the material, resulting in an increase in the amount of methane gas produced.Keywords: Methane gas; Pyrolysis; Plastic; Waste